1997
DOI: 10.1002/mrm.1910370504
|View full text |Cite
|
Sign up to set email alerts
|

Use of voigt lineshape for quantification of in vivo1H spectra

Abstract: Quantification of NMR visible metabolites by spectral modeling usually assumes a Lorentzian or Gaussian lineshape, despite the fact that experimental lineshapes are neither. To minimize systematic fitting errors, a mixed Lorentzian-Gaussian (Voigt) lineshape model was developed. When tested with synthetic FIDs, the Voigt lineshape model gave more accurate results (maximum error 2%) than either Lorentzian (maximum error 20%) or Gaussian models (maximum error 12%). The three lineshape models gave substantially d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 18 publications
3
129
1
Order By: Relevance
“…In the RBFNN method we employed Voigt lineshape. As indicated earlier, Voigt lineshape is a better approximation than Lorentzian or Gaussian alone [18]. It is also worth pointing out that Kanowski et al [46] have also observed lower Cho values with AMARES compared with the LCModel.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In the RBFNN method we employed Voigt lineshape. As indicated earlier, Voigt lineshape is a better approximation than Lorentzian or Gaussian alone [18]. It is also worth pointing out that Kanowski et al [46] have also observed lower Cho values with AMARES compared with the LCModel.…”
Section: Discussionmentioning
confidence: 71%
“…These assumptions are not valid. It is generally agreed that the Voigt lineshape is closer to the observed lineshapes compared to Lorentzian or Gaussian alone [18]. In these studies, we trained the network using the Voigt lineshape.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Usually information concerning the time evolution of some of the parameters is present. Suppose there are S signals, each of which can be modeled by eqn (1). The nth sample of signal s, y ns , is then given by y ns…”
Section: Extension: Time Seriesmentioning
confidence: 99%